ON A GENERIC FRAMEWORK FOR SUSTAINABLE PRODUCT DESIGN: AN APPLICATION TO A FOOD PRODUCT - Ocampo, Lanndon A.; Jumao-as, Ammabelle Marie B.; Labrador, John James T.; Rama, Alona Mae O. (Journal of Agriculture and Technology Management, 2016)
Addressing sustainability has been dominant in several industries in order to meet customer requirements. Together with the rapidly increasing population, the consumption of natural resources has drastically increased resulting in a global issue of scarcity. The food manufacturing industry provides the consumers with a basic need, food firms exert more effort toward sustainability because of the resource scarcity and sustainable product design is a key to realizing sustainability in manufacturing. Several studies have already been conducted in the pursuit of promoting sustainable product design by satisfying the requirements of the TBL. However, there are still significant gaps in a sustainable product designed that are in need to be addressed. First, current literature failed to address the social dimension of sustainability. Second, several stakeholders were not considered in the current literature. Third, current literature failed to use the four-phased QFD. This work attempts to address these gaps by proposing a general framework based on fuzzy QFD-MCDM in a multi-stakeholder multi-phase approach. A case study was conducted in an oil industry in order to test the viability of the methodology. Results show that the oil industry’s top priority on phases I, II, III, and IV are GMP and HACCP accreditation; follow standard specifications, procedures and processes; criticize all aspects of the product and make improvements; and consultation oh experts regularly. It is shown in this work that the framework is viable in implementing sustainable product design.